Influenza vaccination in the elderly. - Morgan, R. (BMJ Group, 1996)
There is overwhelming evidence for the clinical efficacy of the influenza vaccine, especially in the elderly with chronic disease, reducing mortality and hospital admissions. There is also evidence to suggest that the influenza vaccine may be beneficial in the healthy elderly. There is some evidence to suggest that the antibody response in the elderly to the vaccine may decrease with increasing age, although there are several confounding factors that have not been taken into account in many of these studies. That aside, even if antibody response is not as good as that in younger people, the evidence that vaccination saves lives and reduces morbidity in the elderly means that the vaccination should be offered to elderly patients at high risk and perhaps even to the elderly healthy population. Although vaccination of an elderly at-risk patient does not necessarily mean that that particular patient will mount an appropriate antibody response, a significant number of elderly patients will respond appropriately. Serious side-effects from vaccination are extremely rare and the more common side-effects are mild and self-limiting. Increasing the number of elderly people receiving the influenza vaccination will not only result in cost savings for the National Health Service in terms of reduced hospitalisation but, more significantly, the elderly will benefit in terms of reduced morbidity and mortality.